Behaviour of two-way partially prestressing waffle slab incorporated with wire mesh (BRC) / Mohd. Tarmizi Abd. Wahab (Faculty of Civil Engineering, 1991)
This experimental project consists of preparing, fabricating and testing of two-way partially prestressing waffle slab incorporated with wire mesh (BRC) test specimens (simply supported at two sides) under the Knife Edge Load (K.E.L) cyclic loading process. Three different types of test specimens, namely WS01, WS02 and WS03 are similar in overall size but having different sizes and numbers of waffles and ribs within them. The performances or behaviour of the test specimens are examined by load-deflection relationship, load-strain relationship, deflection and strain under load reversals and the ultimate and service loads of each slab system. The experimental results obtained indicated that the presence of increased number of ribs will result in an improved overall performance by the test specimens.